ANALYSIS OF RAW DATA RETURNED BY MOST USED ONLINE PUBLIC OPINION POLLS TOOLS - Gabriela-Lucica MĂRGĂRIT; Radu Cristian TOMA; Diana GROPOȘILĂ-CONSTANTINESCU; Dana BARBA; Gabriela POPA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The appearance and evolution of the questionnaire are strictly linked to the history of statistics as a science. Why is the questionnaire related to the history of statistics? As the questionnaire is not a simple list of questions, the important part behind the questions is the statistical interpretation of the answers received from respondents. We have entered several platforms of public opinion polling, with the idea of seeking maximum effect with minimum effort, from a beginner’s position – how can an entrepreneur be at the beginning of the road. It was conduct research on how works and what deliverables give several platforms of public opinion polling. Each tool that loaded and launched the opinion poll on the consumption of craft beer gave answers with different characteristics, the only common basis being the choice of the free package. Results from Google Forms, ZoHo Survey, and Survey Monkey were analyzed and compared. Of all these, the easiest to work with and most complete is ZoHo Survey for those who don't want to use subscription services, and with some financial effort for a Survey Monkey subscription.